PENGGUNAAN SWITCH GAME TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS VII D SMP NEGERI 2 PONOROGO - Widiana, Yulia Nur; Jatiningsih, Oksiana; Hermayeni, Hermayeni (Universitas Muhammadiyah Ponorogo, 2023)
This research aims to improve students' critical thinking skills in Pancasila Education subjects through a game-based learning model using switch games. This research was carried out in class VII D of SMP Negeri 2 Ponorogo in the 2022/2023 academic year. The subjects in this research were 33 class VII D students, consisting of 16 girls and 17 boys. The data collection method used is descriptive quantitative by conducting observations, interviews and filling out questionnaires. The use of questionnaires in this research was used to determine students' critical thinking abilities with indicators: (1) have an open mind, (2) have fair thinking, (3) tend to look for reasons, (4) have curiosity, (5) Desire to obtain accurate and correct information (6) have flexibility (7) have concern. This research was carried out in 3 stages, namely, initial conditions, cycle 1 and cycle 2 which consisted of observation, action and reflection. The use of this learning model shows the results of a very significant increase in critical thinking skills seen from the average percentage value of 46.46% then in cycle 2 it increased to 65.30%. Then in cycle 2 students experienced a significant increase of 95.05%. Students have also made changes such as (1) explaining the problem; (2) selecting possible criteria as a solution to the problem; (3) designing alternative solutions; (4) deciding what things will be carried out; (5) reviewing, and (6) monitoring usage.